Story of Tora - Locke, David; Lunna, Abubakari (Tufts Archival Research Center, 2005)
Told by Abubakari Lunna on May 26 and June 3, 1989. Edited by David Locke. Story of the origins of the Tora dance and drumming rhythm, composed for funerals.